MENENTUKAN JENIS PENYAKIT MENGGUNAKAN METODE MAMDANI DENGAN GOLONGAN OBAT YANG SESUAI - Jasri Jasri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2018)
Hypertension is another name for high blood pressure and hypertension can be defined as conditions in which blood pressure is higher than 140/90 millimeters of mercury (mmHG). The figure of 140 mmHG refers to systolic reading, when the heart pumps blood throughout the body. Meanwhile, the figure of 90 mmHG refers to diastolic reading, when the heart is relaxed while refilling its chambers with blood. Fyzzy logic with mamdani method is a method for determining obt that is suitable for the type of hypertension so that hypertension keeps running normally.